Istibdal Harta Wakaf Dari Perspektif Mazhab Syafi'e - Hj Abdullah, Luqman (Jurnal Fiqh, 2010)
Among the most popular modes of developing the waqf property in many muslims countries is istibdal, that is, to exchange the original waqf property with the other one. In the Syafi?i school of law there are discussion among their jurists as to how to develop the waqf property but Istibdal is not a popular option given that there are many rules and juristics considerations should be taken into account in implementing it and in many cases it is not allowed. Among the principles that governing the law of waqf is the subject of waqf cannot be sold or transferred to another party and this principle make istibdal is not applicable within the Syafi?i school methodological framework.